ANALISIS RASIO SOLVABILITAS DAN PROFITABILITAS LAPORAN KEUANGAN UNTUK MENILAI KINERJA PT. BANK RAKYAT INDONESIA, TBK - Harmon Lumbanraja (Jurakunman (Jurnal Akuntansi dan Manajemen), 2020)
Assessment of the financial level of a company can be done by analyzing the company's financial statements. To find out whether the company's financial condition in good condition can be carried out various analyzes, one of which is ratio analysis. The purpose of this study was to determine the financial performance of PT. Bank Rakyat Indonesia Tbk in terms of financial ratio analysis. The analytical method used is descriptive analysis using solvency and profitability ratios. Research data and information were obtained from the Indonesia Stock Exchange. Based on the solvency ratio, PT. Bank Rakyat Indonesia, Tbk. in a good position, that is, the company is able to pay its debts in a timely manner (solvable). Judging from the profitability ratio shows a decrease in profits from 2014 to 2015, this shows that companies fail to generate profits that increase from year to year.